Biological control of Glycaspis brimblecombei (Hemiptera: Aphalaridae) in eucalyptus plantations - Ferreira Filho, Pedro Jose; Wilcken, Carlos Frederico [UNESP]; Vianna Lima, Alexandre Coutinho [UNESP]; Nogueira de Sa, Luiz Alexandre; Carmo, Janaina Braga do; Guerreiro, Julio Cesar; Zanuncio, Jose Cola (Springer, 2015)
The genus Eucalyptus, native to Australia, is the host of psylloid insects such as the red gum lerp psyllid Glycaspis brimblecombei, a major Eucalyptus pest introduced into Brazil among other countries. The encyrtid Psyllaephagus bliteus is a primary parasitoid used in the biological control of G. brimblecombei. This study aimed to determine the parasitism of G. brimblecombei by P. bliteus released in eucalyptus plantations. Investigations were carried out in a 19-ha eucalyptus plantation comprised of 9-year-old Eucalyptus camaldulensis (Myrtaceae) in the municipality of Luiz Antnio, So Paulo State, Brazil. Twenty P. bliteus pairs were released at five points in the study area between May and September 2006 and 2007 approximately every 20 days. For evaluation of parasitism, ten leaves per twig were randomly selected and unparasitized nymphs of G. brimblecombei, mummies (parasitized nymphs of G. brimblecombei) and empty mummies (after emergence of P. bliteus adults) were counted on their abaxial and adaxial parts before and after each release of P. bliteus. The parasitism rates of G. brimblecombei in 2006 and 2007 were 0.21-5.92% and 0.28-7.03% in the control; these values rose to 28.28-78.57% and 30.32-79.34%, respectively, in areas involved in parasitoid release. Parasitism levels of G. brimblecombei nymphs in areas with P. bliteus release were affected by the environmental temperature, which is discussed as a potential limitation to the establishment of this parasitoid and to its effectiveness as a biological control agent.
Keywords: Eucalyptus; Forest pest; Monitoring; Natural enemy; Red gum lerp psyllid